The online portrayal of urban farmers: Professionals' perspectives on their influence on constructing farming-career paths - İlkay Unay-Gailhard; Robert J. Chaskin; Mark A. Brennan (Journal of Rural Studies, 2025)
This research extends existing studies on the role of alternative food movements in supporting new farmers. It focuses on the urban agriculture movement, particularly the online portrayal of urban farmers in social media, and its impact on constructing farming-career paths. Analyses explore the perspectives of professionals (N = 32) involved in urban farming initiatives (practitioners, policy professionals, and beginning urban farmers) in Pennsylvania and Illinois. The study uses qualitative thematic coding and aggregates the theoretical dimensions supported by contemporary career theories. Career aspiration, career intention, and career orientation are the career-construction paths that are the interests of the study. Findings suggest that portrayals of urban farmers are multi-faced: "smallness," "diversity," "guidance by moral values," "innovativeness," and "popularity" are the essential themes explaining farming-career aspirations. Farming-career exposure and career experiments via social media are values that drive planned or unplanned career intentions. The portrayal of urban farmers as moral achievers is perceived as a motivator in career orientation by activating relationally driven (inspirations gathered from online relationships) and protean (self-driven) attitudes. Overall, our study demonstrated that online portrayals of urban farmers can shape perceptions about careers within sustainable sectors, including agriculture-related professions.
Keywords: 630; generational renewal problems; alternative food movements; urban agriculture; social media; youth in agriculture; farming career